Penerapan Digital Literasi Kepada Ibu PKK di Desa Bangsongan - Laely, Nur; Andarini, Marwita; Rahmawati, Fransiska Yunita (STIE Malangkucecwara, 2025)
This community service aims to increase digital literacy among PKK women in Bangsongan Village so that they can utilize technology to support daily activities and business management. Through training involving social media, online information search, and digital-based product marketing, participants were given an understanding of how to use digital devices effectively. The result showed an increase in their ability to use digital applications for various purposes, ranging from communication, business management, to online product marketing. This program is expected to empower village women to face the challenges of the digital world and improve the quality of life and family economy through the maximum use of technology. The sustainability of this training can help improve access to information and open up wider business opportunities for the village community.